Whole-exome sequencing expands the roles of novel mutations of organic anion transporting polypeptide, ATP-binding cassette transporter, and receptor genes in intrahepatic cholestasis of pregnancy - Liu, Xianxian; Zheng, Jiusheng; Xin, Siming; Zeng, Yang; Wu, Xiaoying; Zeng, Xiaoming; Lai, Hua; Zou, Yang (Frontiers in Genetics, 2022)
Background: Intrahepatic cholestasis of pregnancy (ICP) is associated with a high incidence of fetal morbidity and mortality. Therefore, revealing the mechanisms involved in ICP and its association with fetal complications is very important. Methods: Here, we used a whole-exome sequencing (WES) approach to detect novel mutations of organic anion transporting polypeptide (OTAP) genes, ATP-binding cassette transporter (ABC) genes, and receptor genes associated with ICP in 249 individuals and 1,029 local control individuals. Two available tools, SIFT and PolyPhen-2, were used to predict protein damage. Protein structuremodeling and comparison between the reference and modified protein structures were conducted by SWISS-MODEL and Chimera 1.14rc software, respectively. Results: A total of 5,583 mutations were identified in 82 genes related to bile acid transporters and receptors, of which 62 were novel mutations. These novel mutations were absent in the 1,029 control individuals and three databases, including the 1,000 Genome Project (1000G_ALL), Exome Aggregation Consortium (ExAC), and Single-Nucleotide Polymorphism Database (dbSNP). We classified the 62 novel loci into two groups (damaging and probably damaging) according to the results of SIFT and PolyPhen-2. Out of the 62 novel mutations, 24 were detected in the damaging group. Of these, five novel possibly pathogenic variants were identified that were located in known functional genes, including ABCB4 (Ile377Asn), ABCB11 (Ala588Pro), ABCC2 (Ile681Lys and Met688Thr), and NR1H4 (Tyr149Ter). Moreover, compared to the wild-type protein structure, ABCC2 Ile681Lys and Met688Thr protein structures showed a slight change in the chemical bond lengths of ATP-ligand binding amino acid side chains. The combined 32 clinical data points indicate that the mutation group had a significantly (p = 0.04) lower level of Cl ions than the wild-type group. Particularly, patients with the 24 novel mutations had higher average values of alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), total bile acids (TBA), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) than patients with the 38 novel mutations in the probably damaging group and the local control individuals. Conclusion: The present study provides new insights into the genetic architecture of ICP involving these novel mutations.